2022
DOI: 10.3389/fpsyg.2022.830987
|View full text |Cite
|
Sign up to set email alerts
|

Socioemotional Resources and Mental Health in Moroccan Adolescents: A Person-Centered Approach

Abstract: Mixture modeling technics are not the one and only to perform person-centered analyses, but they do offer the possibility of integrating latent profiles into models of some complexity that include antecedents and results. When analyzing the contribution of socioemotional resources to the preservation of mental health, it is the variable-centered approaches that are the most often performed, with few examples using a person-centered approach. Moreover, if the focus is on the Arab adolescent population, to our k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 75 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…Whitin these studies we can observe that commonly two profiles are extracted, being typically labeled based on their high or low socio-emotional levels. Also, a third profile regularly emerges as an intermediate profile and is analyzed with an exploratory approach given that their levels are not as theoretically normative as the rest of the profiles (e.g., Sudkamp et al, 2017 ; Castro-Kemp et al, 2019 ; Pulido-Martos et al, 2022 ). For example, Castro-Kemp et al (2019) research organized the profiles based on four socio-emotional variables: gratitude, optimism, zest, and persistence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whitin these studies we can observe that commonly two profiles are extracted, being typically labeled based on their high or low socio-emotional levels. Also, a third profile regularly emerges as an intermediate profile and is analyzed with an exploratory approach given that their levels are not as theoretically normative as the rest of the profiles (e.g., Sudkamp et al, 2017 ; Castro-Kemp et al, 2019 ; Pulido-Martos et al, 2022 ). For example, Castro-Kemp et al (2019) research organized the profiles based on four socio-emotional variables: gratitude, optimism, zest, and persistence.…”
Section: Introductionmentioning
confidence: 99%
“…Here they found that the profile with lowest levels of optimism presented lower levels of socioemotional health and greater emotional and behavioral school-related difficulties. The work of Pulido-Martos et al (2022) self-esteem and emotional intelligence are considered as socioemotional resources. They found a profile with low levels socio-emotional resources that also presented the lowest levels of perceived social support (from parents, peers, and teachers), self-emotional and others appraisal and emotional regulation.…”
Section: Introductionmentioning
confidence: 99%